Hamlet em uma motocicleta: transposições midiáticas das tragédias shakespearianas ocorridas na terceira era de ouro da televisão americana - Lima, Guilherme Fernandes [UNIFESP] (2020)
This dissertation intends to demonstrate the process of medial transposition of selected thematic ensembles of Shakespearean dramaturgy to certain serial narratives from the “third golden age” of American television (MARTIN, 2014). In order to illustrate this process of transposition of symbolic materials, we make use of the theoretical advances conceived by the studies on intermediality - especially those carried out by Irina Rajewsky (2012a, 2012b), specifically directed to literary studies. To this purpose, we delimited this research since The Sopranos (1999-2007) and Sons Of Anarchy (2008-2014) tv-series, together with the plays Hamlet (1599-1601) and King Lear (1606), by William Shakespeare. Our hypothesis of research is based on the recognition of thematic correspondences between the subjects presented by the television series of the referred period and the subjects from the Shakespearean texts - as well as the process of appropriation of these subjects in accordance with the conventions established by television as destination media.